Consumer Decision Making and Marketing Techniques : New Insights into Higher Education in the Digital Era - Widyatmoko Widyatmoko; Tri Esti Rahayuningtyas; Aji Prasojo (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to examine consumer decision-making regarding marketing techniques in higher education institutions in the digital era. As technology advances and competition among universities intensifies, it is crucial for educational institutions to understand the factors influencing prospective students' decisions in choosing a university. The research employs a quantitative approach through surveys involving prospective students from various universities, as well as interviews with education marketing professionals. The findings reveal that the use of social media, personalized digital marketing, and alumni testimonials have a significant impact on influencing prospective students' decisions. This study provides new insights into the importance of adaptive, data-driven marketing strategies for attracting prospective students in the digital age. The significance of this research lies in its ability to offer guidance to higher education institutions in designing more effective and relevant marketing techniques that meet the needs of today's consumers.